Investigating a Quantitative Measure of Student Self-authorship for Undergraduate Medical Education. (December 2019) - Fallar, Robert; Hanss, Basil; Sefcik, Roberta; Goodson, Lucy; Kase, Nathan; Katz, Craig
Construct: In this study, the authors investigated the validity of a quantitative measure of self-authorship among medical students. Self-authorship is a cognitive-structural theory incorporating the ability to define one's beliefs, identity, and social relations to operate in a complex, ambiguous environment. Background: Competency-based medical education (CBME) provides learners with the opportunity to self-direct their education at an appropriate pace to develop and exhibit required behaviors while incorporating functioning relationships with supervisors and trainers. Students must develop skills to adjust and succeed in this educational climate. Self-authorship is a theoretical lens that is relevant to identifying the development of the skills necessary to succeed in a CBME curriculum. Understanding the level of attained self-authorship by medical students can provide important information about which professional characteristics are more prevalent among those who are more self-authored and about how students succeed in medical school. Although there are calls in the extant literature for the application of self-authorship in medical education, there is no quantitative measure to assess its development among medical students. Approach: The authors developed a survey to measure self-authorship, including a free text question regarding the thought process around a hypothetical ethical situation during training. Data were collected in 2014 and 2015 from undergraduate medical students and analyzed using factor analysis and qualitative analysis of the free text. Validity evidence was sought regarding content, internal structure, and relationships to other variables. Results: Analysis supports the use of a 22-item instrument to assess 3 constructs of self-authorship: asserting independence and autonomy, knowledge processing, and sense of self in ethical situations. Content analysis of text responses supported the ability of the instrument to separate development, or a lack thereof, of self-authorship. Conclusions: The authors identified an instrument that measures multidimensional, higher-order characteristics that intersect with self-authorship. This instrument can be useful at a macro level for curricular and student assessment of self-authorship. Development of these characteristics can help foster success in a CBME environment and support curricular efforts in this regard. Understanding a student's level of self-authorship can help identify areas for support as well as allow for comparisons of different student characteristics.